Complex sleeve lobectomy has the same surgical outcome when compared with conventional lobectomy in patients with lung cancer. (9th January 2020) - Inci, Ilhan; Benker, Martina; Çitak, Necati; Schneiter, Didier; Caviezel, Claudio; Hillinger, Sven; Opitz, Isabelle; Weder, Walter
Abstract: OBJECTIVES: No significant data are available to assess whether complex sleeve lobectomy (complex-SL) can be considered comparable to conventional lobectomy (CL) in terms of surgical outcome. The purpose of this study was to compare surgical and oncological outcomes of complex-SL with CL in patients with lung cancer. METHODS: Between 2000 and 2015, a total of 568 patients who underwent open CL (defined as resection of only 1 lobe) and 187 patients who underwent SL were analysed. The SL group was divided into 2 subgroups: standard-SL (bronchial SL, n = 106) and complex-SL ( n = 81) (defined as bronchial sleeve resection together with another surgical intervention: bronchovascular SL, n = 40; vascular SL, n = 26; atypical bronchoplasty with resection of more than 1 lobe, n = 12; bronchial SL + chest wall resection, n = 3). RESULTS: The complex-SL group had more patients with chronic obstructive pulmonary disease (COPD) (25.9% vs 12.5%, P = 0.001), neoadjuvant treatment (39.5% vs 12.0%, P < 0.001), advanced-stage non-small-cell lung cancer (53.2% vs 33.1%, P = 0.001) and low preoperative forced expiratory volume in 1 s (77.2% vs 84.3%, P = 0.004) than the CL group. The overall surgical mortality (in-hospital or 30-day) was 2.6% ( n = 20); it was 2.8% for CL and 2.8% for complex-SL. Postoperative complications occurred in 34.9% of the CL group and 39.5% of the complex-SL group ( P = 0.413). The pulmonary complication rate was similar between the groups (24.1% for CL, 27.2% for complex-SL, P = 0.552). The 5-year survival in the CL group was 57.1%, and in the complex-SL group it was 56.2% ( P = 0.888). Multivariate analysis showed that TNM stage ( P < 0.001) and N status ( P < 0.001) were significant and independent negative prognostic factors for survival. CONCLUSIONS: Complex-SL had a comparable outcome to CL, although the complex-SL group had more patients with advanced-stage NSCLC, low preoperative forced expiratory volume in 1 s and COPD.